Perlakuan Akuntansi Aset Biologis Berdasarkan PSAK No. 69 Tentang Agrikultur Pada PT. Sinar Halomoan Kab. Padang Lawas - Defi Rahayu; Saparuddin Siregar; Nurul Inayah (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This research aims to find out how biological asset accounting is treated (recognition, measurement, disclosure and presentation) at PT. Sinar Halomoan Kab. Padang Lawas. This research uses a qualitative descriptive method, this method is used to view and describe the company's condition systematically. Data collection techniques using observations, interviews and documentation studies, namely annual financial report data for the 2020 period and then analyzing them so that they can provide suggestions for the future. This research was carried out at PT. Sinar Halomoan which is located in Kab. Padang Lawas, North Sumatra. The research period starts from June 2023 - July 2023. Based on the research results, it can be concluded that the Financial Report of PT. Sinar Halomoan is not yet in accordance with PSAK 69 regarding the Measurement, Presentation and Disclosure of Biological Assets, where the company still measures its Biological Assets using Acquisition Price so that PT. Sinar Halomoan has not disclosed profits or losses at the time of initial recognition of its biological assets.